The Molecular Diagnosis Protocols of New Coronavirus (COVID-19); Specificity and Sensitivity an Overview - Ahmed Hama, Abdullah; Abdulrahman Mohammed, Othman; Mahmud Ali, Fatima; Hamid Shareef, Osama; Muhammad Wli, Sardar; Sharif, Sabiha; Ahmed Qadir, Syamand (Kurdistan Journal of Applied Research, 2020)
Acute respiratory tract infection is a common public health concern worldwide a new emerging contagious virus (COVID-2019) or SARSC- 2 causing a pandemic pneumonia outbreak, The main transmission route of this virus is through droplets from respiratory made during sneezing or coughing of infected people like the recent viral infection of severe acute respiratory syndrome (SARS-CoV1) and the Middle East respiratory syndrome (MERS). Many epidemiological factors have a crucial role in promoting the transmission of the COVID-2019 that makes the disease as an emerging and global alarming against this new coronavirus. Early diagnosis of the etiological agents is critical for appropriate management, controlling plan, protection, and treatment. The new outbreak of COVID-19 can be detected by different molecular protocols. Quantitative polymerase chain reaction (qPCR) is the recommended technique used with varied sensitivity due to primers variation and specimen type. The reliable, high specific and sensitive diagnosis protocols are necessary for an emerging control plan. This study will review and explore the most available methods of molecular identification and primers for the diagnosis of the new coronavirus (COVID-19). This review will also open the new clues to develop and select appropriate diagnosis panel and specific primers for new coronavirus. In conclusion of this review, the RNA dependent RNA polymerase (RdRp) and RdRp/Hel protocols will be valuable to distinguish the COVID-19 from the SARS-CoV and the other respiratory viral pathogens.